Directed evolution of the 5'-untranslated region of the phoA gene in Escherichia coli simultaneously yields a stronger promoter and a stronger Shine-Dalgarno sequence. - Huang,X; Zhang,X-E; Zhou,Y-F; Zhang,Z-P; Cass,AEG (Biotechnol J, 2006)
Directed evolution has been widely applied for gene improvement through random mutagenesis of coding sequences. Through error-prone PCR both in the coding sequence and the regulatory sequence of E. coli alkaline phosphatase, the cellular enzyme activity has been efficiently enhanced. Sequence analysis revealed that the resultant mutant 34-B12, which showed a sevenfold increased enzyme activity at the cellular level, contains three mutations in the regulatory sequence and another three mutations in the coding sequence. Activity assays of the enzyme containing the corresponding amino acid substitutions proved that the amino acid mutations contribute only to a small portion to the increased cellular enzyme activity. So the mutations in the 5'-untranslated region were analyzed separately and combinationally. The results suggested that one mutation yielded a stronger promoter and the other two mutations both elevated the E. coli alkaline phosphatase expression at the translational level; moreover, a stronger Shine-Dalgarno sequence was generated.